A fast and sensitive method for the continuous in situ determination of dissolved methane and its [delta]13C-isotope ratio in surface waters - Kleint, Jan F.; Schiller, Amanda; Greule, Markus; Keppler, Frank; Isenbeck-Schröter, Margot (Limnology and oceanography. Methods, 2018)
A fast and sensitive method for the continuous determination of methane (CH4) and its stable carbon isotopic values (δ13C-CH4) in surface waters was developed by applying a vacuum to a gas/liquid exchange membrane and measuring the extracted gases by a portable cavity ring-down spectroscopy analyser (M-CRDS). The M-CRDS was calibrated and characterized for CH4 concentration and δ13C-CH4 with synthetic water standards. The detection limit of the M-CRDS for the simultaneous determination of CH4 and δ13C-CH4 is 3.6 nmol L−1 CH4. A measurement precision of CH4 concentrations and δ13C-CH4 in the range of 1.1%, respectively, 1.7‰ (1σ) and accuracy (1.3%, respectively, 0.8‰ [1σ]) was achieved for single measurements and averaging times of 10 min. The response time τ of 57 ± 5 s allow determination of δ13C-CH4 values more than twice as fast than other methods. The demonstrated M-CRDS method was applied and tested for Lake Stechlin (Germany) and compared with the headspace-gas chromatography and fast membrane CH4 concentration methods. Maximum CH4 concentrations (577 nmol L−1) and lightest δ13C-CH4 (−35.2‰) were found around the thermocline in depth profile measurements. The M-CRDS-method was in good agreement with other methods. Temporal variations in CH4 concentration and δ13C-CH4 obtained in 24 h measurements indicate either local methane production/oxidation or physical variations in the thermocline. Therefore, these results illustrate the need of fast and sensitive analyses to achieve a better understanding of different mechanisms and pathways of CH4 formation in aquatic environments.